2022
DOI: 10.21203/rs.3.rs-1576641/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dynamic contrast-enhanced MR imaging of breast cancer: the correlation between mono-exponential DWI parameters and semi-quantitative TIC characteristics

Abstract: Background To investigate the relationship between mono-exponential diffusion- weighted imaging (DWI) parameters and time-intensity curve (TIC) characteristics generated from dynamic contrast-enhanced (DCE) MRI of breast cancer. Materials and Methods A total of 108 patients with breast cancer were prospectively enrolled in this study. All patients underwent DWI and DCE-MRI examination. Patients were divided into untypical TIC and untypical TIC groups; untypical TIC pattern was defined as a wash-in/plateau cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Actually, a recent study showed that the type II curve (intermediate risk of malignancy) was present not only in malignant lesions (50%) but also in 29.3% of benign lesions [10]. The overlap of TIC patterns between benign and malignant diseases in clinical settings may occur, resulting in inaccurate diagnosis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, a recent study showed that the type II curve (intermediate risk of malignancy) was present not only in malignant lesions (50%) but also in 29.3% of benign lesions [10]. The overlap of TIC patterns between benign and malignant diseases in clinical settings may occur, resulting in inaccurate diagnosis [11].…”
Section: Introductionmentioning
confidence: 99%